Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00586-011-1874-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic markers predicting the outcome of brace treatment in patients with adolescent idiopathic scoliosis

Abstract: Purpose To investigate whether the predisposition genes previously reported to be associated with the occurrence or curve severity of adolescent idiopathic scoliosis (AIS) play a role in the effectiveness of brace treatment. Method A total of 312 AIS patients treated with bracing were enrolled in this study. The Cobb angle of the main curve was recorded at the beginning of brace treatment as well as at each follow-up. The patients were divided into two groups according to the outcome of brace treatment (succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
2
35
1
1
Order By: Relevance
“…However, Tang et al demonstrated no association of XbaI polymorphism, either with occurrence, or with Cobb angle, nor with anthropometric measurements in the Chinese Han population [16]. In 2011, Xu et al performed a study in the Chinese population and suggested that the X (G) allele at the rs9340799 might be a potential genetic marker, predicting the outcome of brace treatment for IS [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, Tang et al demonstrated no association of XbaI polymorphism, either with occurrence, or with Cobb angle, nor with anthropometric measurements in the Chinese Han population [16]. In 2011, Xu et al performed a study in the Chinese population and suggested that the X (G) allele at the rs9340799 might be a potential genetic marker, predicting the outcome of brace treatment for IS [17].…”
Section: Introductionmentioning
confidence: 99%
“…One study in an independent Japanese population found a marginally significant association between rs9340799 and curve severity represented by the mean Cobb angle (p = 0.0509) [10], while two other studies in Chinese [9] and Polish Caucasian [11] populations found no association. There is also limited evidence that rs9340799 may play a role in the effectiveness of brace treatment, where patients with the G allele were significantly more likely to be resistant to brace treatment [26], and in the risk for operative treatment and curve progression [7]. These clinical correlations have potential applications in personalized medicine; genetic information can be incorporated into risk prediction models for the prevention [27] and treatment of AIS, such as genetic testing for the risk of severe spinal curve progression [28].…”
Section: Discussionmentioning
confidence: 95%
“…Currently, the standard of care for AIS patients includes the following options: observation, for patients with a small curve or skeletal maturity; brace treatment, for those with a mild or moderate curve and skeletal immaturity; and surgical correction, for those with a severe curve [2]. Until now, brace treatment has served as a vital non-surgical procedure for immature AIS patients with a mild or moderate curve, because bracing can effectively halt curve progression and prevent surgical intervention in some cases [17,19,23,31,34,35]. To date, several types of brace devices have been developed, such as the Milwaukee [17], Boston [19], Charleston [25], Providence [32], Rosenberger [24], Wilmington [1] and Chêneau [34].…”
Section: Introductionmentioning
confidence: 99%